Still Waiting for the DREAM: The Justice of Punishing Undocumented Immigrant Students - Annand, Katie (2008)
An estimated 50,000 to 65,000 undocumented immigrant students graduate from high schools in the United States each year. Yet, upon reaching graduation, undocumented immigrant students, who oftentimes grew up in the United States and consider this country their home, face significant obstacles: current federal laws effectively bar access to higher education for many of these students by imposing substantial financial barriers and by preventing these students from obtaining legal residency, foreclosing federal financial aid and many career options requiring work authorization. Legislators have responded to student efforts to seek equal access to higher education by proposing the DREAM Act. This Act would remove considerable financial barriers undocumented immigrant students face in pursuing a higher education as well as establish a path to legal residency for qualifying students. The DREAM Act, however, has faced strong opposition from those who believe undocumented immigrant students should not be rewarded for breaking the law. This Note proposes that current federal laws punish undocumented immigrant students by attaching culpability to an act beyond their control: entering the country illegally with their families. In response, this Note argues that due to the students' lack of culpability-and lack of voluntariness in the original violation of the law-the punishment of undocumented youth is not justified by popular theories of punishment